Effect of VEGFC on lymph flow and inflammation‐induced alveolar bone loss. Issue 3 (10th June 2020) - Wang, Hua; Chen, Yuyi; Li, Wenlei; Sun, Lian; Chen, Hongyu; Yang, Qiudong; Zhang, Hang; Zhang, Weibing; Yuan, Hua; Zhang, Hengwei; Xing, Lianping; Sun, Wen
Abstract: The lymphatic system plays a crucial role in the maintenance of tissue fluid homeostasis and the immunological response to inflammation. The effects of lymphatic drainage dysfunction on periodontitis have not been well studied. Here we show that lymphatic vessel endothelial receptor 1 (LYVE1) + /podoplanin (PDPN) + lymphatic vessels (LVs) are increased in the periodontal tissues, with accumulation close to the alveolar bone surface, in two murine periodontitis models: rheumatoid arthritis (RA)‐associated periodontitis and ligature‐induced periodontitis. Further, PDPN + /alpha‐smooth muscle actin (αSMA) − lymphatic capillaries are increased, whereas PDPN + /αSMA + collecting LVs are decreased significantly in the inflamed periodontal tissues. Both mouse models of periodontitis have delayed lymph flow in periodontal tissues, increased TRAP‐positive osteoclasts, and significant alveolar bone loss. Importantly, the local administration of adeno‐associated virus for vascular endothelial growth factor C, the major growth factor that promotes lymphangiogenesis, increases the area and number of PDPN + /αSMA + collecting LVs, promotes local lymphatic drainage, and reduces alveolar bone loss in both models of periodontitis. Lastly, LYVE1 + /αSMA − lymphatic capillaries are increased, whereas LYVE1 + /αSMA + collecting LVs are decreased significantly in gingival tissues of patients with chronic periodontitis compared with those of clinically healthy controls. Thus, our findings reveal an important role of local lymphatic drainage in periodontal inflammation‐mediated alveolar bone loss. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.